2019
DOI: 10.1371/journal.pone.0225133
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant prescriptions, discontinuation, depression and perinatal outcomes, including breastfeeding: A population cohort analysis

Abstract: ObjectivesTo explore associations between exposure to antidepressants, their discontinuation, depression [medicated or unmediated] and preterm birth [<37 and <32 weeks], small for gestational age (SGA) [<10th and <3rd centiles], breastfeeding [any] at 6–8 weeks.MethodsDesign: A population-based cohort study.Setting: The Secure Anonymised Information Linkage [SAIL] databank in Wales, linking maternal primary care data with infant outcomes.Participants: 107,573, 105,331, and 38,725 infants born 2000–2010 with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 86 publications
(137 reference statements)
3
24
0
2
Order By: Relevance
“…Furthermore, our results support the view that in mothers on SSRI therapy the low breast milk supply may be accounted for by the locally produced 5-HT [39,40]. Consistent with this notion, in a most recent population-based cohort study Jordan et al demonstrated that exposure to depression or to antidepressants particularly to high dose SSRIs during pregnancy increased the risks of exclusive formula feeding at 6-8 weeks [41].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our results support the view that in mothers on SSRI therapy the low breast milk supply may be accounted for by the locally produced 5-HT [39,40]. Consistent with this notion, in a most recent population-based cohort study Jordan et al demonstrated that exposure to depression or to antidepressants particularly to high dose SSRIs during pregnancy increased the risks of exclusive formula feeding at 6-8 weeks [41].…”
Section: Discussionsupporting
confidence: 89%
“…At present it is difficult to address these concerns directly, due to a dearth of empirical evidence focused specifically on the population of birth mothers in question and their pregnancies. Although there is a wealth of literature reporting an association between socio-economic status, mental health difficulties, substance use (alcohol and drugs) and pregnancy [8][9][10], this literature is insufficiently focused on the population of birth mothers in question. For example, the published literature offers no insights about the timing of this particular population of women's engagement with ante-natal services, despite the fact that pregnancy provides an absolutely critical space for intensive work to address parental vulnerabilities associated with infant removal.…”
Section: Introductionmentioning
confidence: 99%
“…Altered maternal-child interactions are reported when women suffer from postpartum depression and comorbid anxiety. Decreased breastfeeding, or premature cessation of it, has been observed in women with depression before or during pregnancy (Wallenborn et al, 2018;Jordan et al, 2019). Genetic rodent models with depression-like behavior show some of the characteristics of these altered interactions, as seen with the decreased nursing of WMIs compared to WLIs.…”
Section: Discussionmentioning
confidence: 99%